Improved GaAs nanowire solar cells using AlGaAs for surface passivation - Lee, Y; Li, Z; Fu, L; Parkinson, P; Vora, K; Tan, H; Jagadish, C (2012)
Semiconductor nanowire solar cells (NWSCs) have attracted significant interests owning to their potential in the applications of high-performance solar cells. Here, we report improved GaAs solar cell performance using a high-quality AlGaAs shell for surface passivation. The device exhibits an open-circuit voltage (Voc) of 0.70V, a short-circuit current density (Jsc) of 9.79 mA/cm2, a fill factor (FF) of 0.52, and a total power conversion efficiency (η) of 4.22%. This work suggests a promising route to optimize NWSCs. © 2012 IEEE.